Changes in the Composition of the WIG20 and mWIG40 Indices and the Operational Performance of Newly Added Companies - Blaszke, Ewa (Wpływ zmian składu indeksu WIG20 i mWIG40 na wyniki operacyjne dodanych spółek, 2024)
Aim: This article investigates whether the transition of companies from the mWIG40 index to the more prestigious WIG20 index affects their operational efficiency. Methodology: The study analyzes 17 companies that transitioned from mWIG40 to WIG20 between 2000 and 2020. Four operational efficiency indicators were calculated for each company in the four quarters preceding and following the index change. The t-Student test was applied to determine whether this shift had a statistically significant impact on operational performance. Findings: The analysis did not reveal statistically significant changes in the majority of the examined operational efficiency indicators following the transition. The exception was the net income on sales/total revenue ratio, which demonstrated statistically significant differences in certain quarters after the index change. Implications: These findings support the hypothesis that the transition of a company from the mWIG40 index to WIG20 does not lead to an improvement in its operational results. The results suggest that investors should carefully evaluate other factors when interpreting index transitions as signals of improved corporate performance. Originality/value: This study contributes to the existing literature by providing empirical evidence on the relationship between stock index transitions and operational performance in the Polish capital market, addressing a relatively underexplored research area.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 1, s. 13-23
Keywords: stock index composition; company's financial performance; operational performance; skład indeksów giełdowych; wynik spółek; efektywność operacyjna